Quantitative SUMO proteomics identifies PIAS1 substrates involved in cell migration and motility - Chongyang Li (Nature Portfolio, 2020)
PIAS1 is an E3 SUMO ligase involved in various cellular processes. Here, the authors use quantitative proteomics to identify potential PIAS1 substrates in human cells and elucidate the biological consequences of PIAS1-mediated SUMOylation of vimentin.